PSXII-30 Suffolk Ram Yearling Breeding Potential Evaluation. (7th December 2018) - Sawyer, R; Konetchy, D; Menegatti Zoca, S; Falk, J; Vinci, D; Murdoch, B
Abstract: Selection of potential breeding rams is a difficult task, often choosing replacement ram lambs at time of weaning. However, at weaning, it is not clear what their full potential as sires might be. The objective of this study was to create an index to determine which of the ram lambs selected at the University of Idaho (UI) flock had the higher breeding potential based on a multiple characteristics assessment. A group of 11 purebred Suffolk ram lambs from the 2017 UI lambing year were selected from the flock as potential breeding rams, based on conformation traits. The production goals at the UI are focused on meat, conformation, uniformity, ease of breeding, and fecundity traits to meet a 200% lambing crop. All the ram lambs were from the same flock and sired by one of two twin rams. As the ram lambs grew individual performances were measured by growth rates, carcass scan data, conformation scores, breeding soundness exam (BSE) and sire estimated breeding values (EBV). The data was used to create an index designed to evaluate the quality of performance and the potential use as breeding stock. The index was used to rank the yearling rams 1 through 11, (1 being the highest performance/breeding potential, and 11 the lowest). Characteristics considered for ranking were birth type, average daily gain, BSE, loin depth, ribeye area, rib fat thickness, and structural conformation. In conclusion, the index was used to rank the rams to conclude that 3 rams should be excluded as potential breeders. The information gained allowed for recommendations to the UI flock managers on which rams should be kept. In addition, evaluating more than a single characteristic allowed for better understanding of the potential performance outcomes and aided the selection for traits that are difficult to measure and perpetuate in the flock.